Cell Death and Organ Injury: The Example of the Kidney - Giovanna Priante; Lisa Gianesello; Monica Ceol; Dorella Del Prete; Franca Anglani (Recent Research Advances in Biology Vol. 10, 2021)
When tissues are damaged, they usually heal. The cellular responses towards healing require the prior recognition that damage has occurred. Apoptotic cell death is usually a response to the cell’s microenvironment. In fact, prolonged cellular stress may activate homeostatic repair processes, or cells may undergo apoptosis when overwhelmed by the stress. In the kidney apoptosis contributes to parenchymal cell loss in the course of acute and chronic renal injury, but does not trigger an inflammatory response. On the contrary if inflammation happens, we can have necrosis which differs from apoptosis by the breakdown of integrity of the plasma membrane so necrotic cell death is accompanied by the release of unprocessed intracellular content, including cellular organelles, which are highly immunogenic proteins. The relative contribution of apoptosis and necrosis to injury varies, depending on the severity of the insult. Regulated cell death may result from immunologically silent apoptosis or from immunogenic necrosis. Recent advances have enhanced the most revolutionary concept of regulated necrosis. Several modalities of regulated necrosis have been described, such as necroptosis, ferroptosis, pyroptosis, parhanatos, mitochondria permeability transition regulated necrosis and NETosis. In cell death, mitochondria, which are widely known for their canonical role in cellular respiration and oxidative phosphorylation, are also recognized as key contributors in the cell death pathway, with a central role in detecting and integrating signals from the environment to trigger adaptive and compensatory responses in cells. Thus, mitochondrial damage and dysfunction are identified as one of the pathogenic events in a variety of diseases, including both chronic and acute kidney diseases. Therefore, we review the different modalities of cell death in kidney injury, pointing in particular to converging pathways of cell death and evidencing that a combination therapy targeting multiple cell-death pathways may lead to new opportunities for therapeutic intervention.